THE FUTURE PROSPECTS OF BIOECONOMY - Murodov Abduvohid (Лучшие интеллектуальные исследования, 2024)
Annotation: The future prospects of bioeconomy are promising, as society increasingly looks for sustainable solutions to address environmental challenges and create a more circular economy. Bioeconomy refers to the use of renewable biological resources, such as plants, animals, and microorganisms, to produce food, energy, and materials. In this article I have researched the current issues related to the bioecoomy and explained my innovative solutions to tackle them.